Design of Oxygen and Carbon Dioxide Monitoring System in Cocoa Fermentation with Internet of Things and Automatic Stirring System - Sabila, Liya Yusrina; Linggar Rahmat Dwiyono; Agus Rahman Hakim; Abi Nazli Karuana; Dhias Cahya Hakika; Farrah Fadhillah Hanum (Jurusan Teknik Elektro Universitas Andalas, 2025)
In some areas in Indonesia, more traditional cocoa farmers have yet to carry out special monitoring of O2 and CO2 levels during fermentation because the practices and technologies used by cocoa farmers can vary significantly in different regions and levels of development. The right amount and level of O2 and CO2 can regulate the activity of microorganisms and affect the overall fermentation process. The fermentation box is made using a wooden board measuring 50x50 cm and is equipped with a stirring blade inside. The sensors used are the Gravity O2 I2C Sensor and the CO2 Sensor MG-118, with a high torque D.C. motor as the stirring blade drive. The results of monitoring and controlling the stirrer are carried out using the Blynk IoT platform or directly on the fermentation box. The tests carried out include testing on an empty fermentation box and testing on the fermentation process of 1kg and 6kg cocoa. After carrying out the testing process, the sensors and IoT systems created can work optimally. The sensor test results in the cocoa fermentation process show a change in CO2 concentration, initially 400 ppm, increasing to a maximum of 1600 ppm. Meanwhile, the O2 concentration remains stable at 20-21% vol, and the stirrer can work optimally. The D.C. motor-driven stirrer can operate effectively with a stirrer response time of 2 seconds and a stirring efficiency of 95% at both fermentation loads (1kg and 6kg). The monitoring system integrated with the Blynk IoT platform shows a gas measurement accuracy rate of 98%, making it easier for cocoa farmers to monitor and control the fermentation process more accurately. The effectiveness of this system can improve the quality of cocoa fermentation results by optimizing fermentation conditions through the right O2 and CO2 levels.